Vaccination Against Diphtheria and Tetanus as a Way to Activate Adaptive Immunity in Children with Solid Tumors - Kostinov, Mikhail Petrovich; Akhmatova, Nelli Kimovna; Karpocheva, Svetlana Victorovna; Vlasenko, Anna Egorovna; Polishchuk, Valentina Borisovna; Kostinov, Anton Mikhailovich (Frontiers in Immunology, 2021)
Early studies on vaccination of children with oncological diseases were dedicated to nothing but assessment of safety and immunogenicity of the drug. Mechanisms of the post-vaccination immune response were not investigated. The study involved 41 patients aged 7-15 years treated against solid tumors two or more years ago. Of these, 26 were vaccinated against diphtheria and tetanus with ADS-m toxoid. 15 children (i.e., controls) were not vaccinated. The vaccination tolerability and clinical characteristics of the underlying disease remission ware assessed. Lymphocyte subpopulations were investigated over time by flow cytometry in 1-6-12 months. IgG anti-diphtheria and anti-tetanus toxoids levels were assessed by ELISA. Within the first day of the post-vaccination period, 2 (7.7%) children demonstrated moderate local reactions and increased body temperature (up to 38.0 ºС). Relapse and metastasis were not mentioned within a year after immunization. An increase in concentration of IgG antibodies, maintained for 12 months, were noted (2.1 [1.3-3.4] IU/ml against diphtheria (p <0.001), 6.4 [2.3-9.7] IU/ml against tetanus (p <0.001)). In contrast to healthy children, those with a history of cancer demonstrated a decrease in relative number of mature T-lymphocytes, as well as in absolute number of cytotoxic T-cells and B-lymphocytes. In a month after the revaccination, a significant increase in absolute (p = 0.04) and relative (p = 0.007) numbers of T-lymphocytes and T-helpers was revealed. In a year these values decreased to baseline levels. As for helpers, they decreased below baseline and control values (p = 0.004). In a year after the vaccination there was a significant (p = 0.05) increase in lymphocyte level with a decrease in number of NK cells and B cells as compared with controls. Revaccination against diphtheria and tetanus promoted proliferation of total lymphocytic cell pool along with restoration of T-lymphocyte subpopulation in children with a history of solid tumors. ADS-m toxoid has a certain nonspecific immunomodulatory effect. These findings are important, also in the midst of the coronavirus pandemic.